Evaluation of the capabilities and damage risk of cleaning methods for micro-CMM stylus tips - Feng, Xiaobing; Lawes, Simon; Kinnell, Peter K. (2015)
The dimensional accuracy of a micro-CMM is significantly affected by contamination adhered to the stylus tip during use. Contaminant particles can cause dimensional errors that are orders of magnitude greater than those reported in the literature. To reduce such errors, this study evaluates the suitability of three cleaning methods (brushing, laser cleaning and snow cleaning) for removing surface contamination on a micro-CMM stylus tip. The cleaning capability of each method is experimentally investigated. Due to the fragile nature of the styli, possible damage (mechanical and thermal) to the tip is assessed. Overall, snow cleaning was found to possess higher cleaning capability and lower risk of damage than the other two methods.